A FLEXIBLE SPECTRALLY CONSTRAINED MULTIBAND MULTICARRIER SIGNAL DESIGN AND CHANNEL ESTIMATION FOR CHANNEL SOUNDING APPLICATIONS - IQBAL, ASIF (2023)
The problem of channel sounding and channel characterization for wireless communication has been studied for many years. Lately, software-defined radios (SDRs) are being exploited for channel sounding to obtain channel impulse response (CIR). The SDRs allow cost-effective and efficient implementation of orthogonal frequency-division multiplexing (OFDM) based sounding systems. However, there are still vital challenges that need to be addressed. First, the SDR hardware has limited system bandwidth. Second, the OFDM waveform suffers from a high Peak-to-Average Power Ratio (PAPR). Third, radio spectra are getting congested, and regulations on spectrum allocation impose spectrum constraints on the sounding waveform. This work addresses all these challenges by introducing a new flexible spectrally constrained multiband multicarrier signal design and its use in channel estimation for channel-sounding applications.